African Women's Unique Vulnerabilities to HIV/AIDS : Communication Perspectives and Promises - Fuller, Linda K. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This is an in-depth look at the biomedical, socio-cultural, economic, legal and political, and educational vulnerabilities faced by the population that is most vulnerable to the risk of contracting HIV/AIDS: African women.